CD97 stabilises the immunological synapse between dendritic cells and T cells and is targeted for degradation by the Salmonella effector SteD - Cerny, Ondrej; Godlee, Camilla; Tocci, Romina; Cross, Nancy E.; Shi, Haoran; Williamson, James C.; Alix, Eric; Lehner, Paul J.; Holden, David W. (PLoS pathogens, 2021)
The Salmonella enterica effector SteD depletes mature MHC class II (mMHCII) molecules from the surface of infected antigen-presenting cells through ubiquitination of the cytoplasmic tail of the mMHCII β chain. This requires the Nedd4 family HECT E3 ubiquitin ligase Wwp2 and a tumor-suppressing transmembrane protein adaptor Tmem127. Here, through a proteomic screen of dendritic cells, we found that SteD targets the plasma membrane protein CD97 for degradation by a similar mechanism. SteD enhanced ubiquitination of CD97 on K555 and mutation of this residue eliminated the effect of SteD on CD97 surface levels. We showed that CD97 localises to and stabilises the immunological synapse between dendritic cells and T cells. Removal of CD97 by SteD inhibited dendritic cell-T cell interactions and reduced T cell activation, independently of its effect on MHCII. Therefore, SteD suppresses T cell immunity by two distinct processes.